An assessment of stakeholders value for urban park physical and recreational setting / Nurul Akmaniza Mohd Nasir - Mohd Nasir, Nurul Akmaniza (2017)
Urban park plays a critical role in the development of urban community especially in maintaining their quality of life. However, the local authority may plan, develop and manage the variety of the urban park setting, but its always depend on how actually stakeholders perceived the setting , react towards it and attained the desired benefits. Therefore, the information on how actually stakeholders value the urban park setting is very important to enhance the urban park benefits. This study aimed to assess the value of stakeholders towards the urban park physical and recreational setting. Y Lake Recreational Park was chosen as the study area for its critical role as the only green space provided for the residents in the area. The application of Q methodology in this study was able to solve the diversity of value exists among stakeholders. Q sample was developed based upon Malaysian Planning Guideline for Open Space and Recreation (2013). Photos were presented during sorting process and respondents were asked to sort the photos based on the question given. Data analysis process were done using PQ method software. For the findings, the primary data on the value of urban park were identified as natural value, sense of ownership and comfort value, recreational and health value and lastly, social value. A framework was developed in the study consisting the fundamental ways in enhancing urban park physical and recreational setting to deliver the value effectively. The findings in this study is hoped to be very useful for the local authority such as Majlis Perbandaran Batu Pahat especially and to the Malaysian Department of Town and Country Planning generally.